A method for alleviating membrane fouling in ED

By adding polycatolences to the freshwater chamber of the electrodelidum, adsorbing and inhibiting the growth of the film surface crystal nuclei, solving the problem of the middle membrane dirt in the ED device, and realizing the reduction of the efficient dirt resistance and energy consumption.

CN118929859BActive Publication Date: 2025-01-28NANJING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411421136.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The film surface scaling problem in electrodialysis (ED) devices leads to an increase in membrane potential difference, an increase in membrane stack impedance, and a decrease in ion exchange capacity, limiting its industrial application.

Method used

Add polycatolences to the electro -ostia diaphragm pile of the freshwater room, and the active sites such as CASO4 and MG (OH) 2 such as CASO4 and MG (OH) 2 attached to the membrane surface, disturb the arrangement and integration of calcium and magnesium ions on the surface of the crystal nucleus. Inhibit the growth of the core crystal core.

Benefits of technology

Effectively prevent the scaling of the ionic membrane surface in the ED device, achieve 40 % to 60 % of calcium and magnesium ions, and reduce the operating energy consumption of about 15 % and the operating cost of about 20 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929859B_ABST
    Figure CN118929859B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for alleviating scaling on the membrane surface in ED, the method comprising the following steps: (1) adding polyelectrolytes to high-salinity wastewater to obtain a mixed solution; (2) pumping the mixed solution into the fresh water chamber of the electrodialysis membrane stack, and pumping industrial tap water into the concentrated water chamber of the electrodialysis membrane stack; (3) applying a voltage between the cathode and the anode of the electrodialysis membrane stack to concentrate and reduce the amount of high-salinity water. The present invention can effectively prevent scaling on the membrane surface of the ion exchange membrane in the electrodialysis device by adding a trace amount (<10 mg / L) of polyelectrolytes to the fresh water chamber of the electrodialysis membrane stack, and achieve a scale inhibition rate of 40% to 60% for calcium and magnesium ions. At the same time, when treating the same volume of wastewater, the electrodialysis device can reduce the operating energy consumption by about 15% and save about 20% of the operating cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for alleviating scaling on a membrane surface in an ED, and belongs to the technical field of wastewater treatment. Background Art

[0002] Electrodialysis (ED) is a desalination technology that separates salts by selectively permeating ion exchange membranes through electrically driven directional migration of ions. Due to its excellent separation performance and low energy consumption, ED has been widely used in seawater desalination, lithium extraction from salt lakes, and high-salt water concentration and reduction. However, the easy scaling property of ED is one of the key technical bottlenecks hindering its industrial application. Due to the complexity of high-salt water quality, inorganic ions such as calcium and magnesium in the water will form on the membrane surface in the form of CaSO 4 and Mg(OH) 2 The membrane surface will be precipitated in the form of ions, which will cause scaling on the membrane surface. This scaling phenomenon will not only increase the membrane potential difference and the membrane stack impedance, but also reduce the ion exchange capacity of the membrane, increase the specific energy consumption of ED and reduce the desalination efficiency, thus limiting its industrial application.

[0003] At present, the main methods to prevent ED membrane scaling are chemical cleaning, membrane surface modification, pulse electrodialysis and reverse electrodialysis. Chemical cleaning is to clean the membrane surface with 1wt% to 10wt% hydrochloric acid to dissolve and remove the mineral scale on the membrane surface. Although chemical cleaning can effectively remove membrane scaling, frequent cleaning will not only increase the operation and maintenance cost of the equipment, but also shorten the service life of the membrane and even cause serious secondary pollution problems. Chemical cleaning membrane surface modification is to precisely control the hydrophilicity, roughness and charge density of the membrane surface in order to reduce the crystal growth on its surface. For example, studies have shown that coating a uniform layer of Nafion polymer on the surface of the ion exchange membrane can significantly improve the problem of membrane scaling. Although a large number of studies have shown that membrane surface modification can effectively alleviate membrane scaling, there is no industrialized membrane surface modification technology to solve the problem of membrane scaling in ED. Pulse electrodialysis and reverse electrodialysis are currently the most mature strategies to inhibit membrane scaling. Both of them significantly alleviate the scaling problem on the membrane surface by reducing the ion concentration polarization on the membrane surface and avoiding the oversaturation of inorganic ion concentrations such as calcium and magnesium on the membrane surface. Among them, pulse electrodialysis reduces the ion concentration polarization on the membrane surface by periodic changes in the square wave potential (CN2407824Y); reversal electrodialysis reduces the ion concentration polarization on the membrane surface by periodic changes in the reverse electrode (CN212315664U; CN212315716U). Both operating modes can alleviate the scaling problem on the membrane surface and maintain the membrane flux of the ion exchange membrane. However, this method of potential control poses a huge challenge to the stability of the electrode material and may lead to a significant shortening of the depreciation period of the electrodialysis equipment. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method that can effectively alleviate membrane scaling in ED, which can effectively solve the problem of membrane scaling of ion exchange membranes in electrodialysis devices during high-salt water reduction.

[0005] Technical solution: The method for alleviating membrane scaling in ED according to the present invention comprises the following steps:

[0006] (1) adding polyelectrolyte to high-salinity wastewater to obtain a mixed solution;

[0007] (2) pumping the mixed liquid into the fresh water chamber of the electrodialysis membrane stack, and pumping industrial tap water into the concentrated water chamber of the electrodialysis membrane stack;

[0008] (3) Apply voltage between the cathode and anode of the electrodialysis membrane stack to concentrate and reduce the amount of high-salt water.

[0009] The present invention adds polyelectrolytes into the dilute chamber of the electrodialysis membrane stack, and these polyelectrolytes can adsorb CaSO4 attached to the membrane surface. 4 and Mg(OH) 2 The active sites on the surface of the crystal nucleus disrupt the arrangement and integration process of ions on the surface of the crystal nucleus, thereby effectively inhibiting the growth of crystal nuclei on the membrane surface and further improving the operating stability of the electrodialysis device.

[0010] Wherein, in step (1), the polyelectrolyte is polymerized from acrylic acid, vinyl acetate, acrylamide and sodium methyl methacrylate sulfonate.

[0011] Wherein, the structure of the polyelectrolyte is shown in the following formula:

[0012] The polyelectrolyte is prepared by the following method, and the specific steps are as follows:

[0013] (1.1) Add acrylic acid and sodium methacrylic acid sulfonate to distilled water, and after dissolving, gradually add saturated NaOH solution to the solution, adjust the pH of the reaction solution to 6-7, then raise the temperature to 55° C., add an initiator to the reaction solution, and react at this temperature; the reaction product after the reaction is purified by anhydrous ethanol, and dried to obtain a solid product;

[0014] (1.2) Add the solid product of step (1.1) into deionized water, raise the temperature to 50-100°C, and dropwise add acrylamide, vinyl acetate and initiator into the above solution under stirring. After the addition, keep the temperature for 1-6 hours; after the reaction, reduce the temperature of the reaction solution to below 40°C to preliminarily obtain a polyelectrolyte aqueous solution.

[0015] (1.3) In the final application, the cooled polyelectrolyte aqueous solution is directly added into the high-salinity wastewater.

[0016] Wherein, in step (1.1), the initiator is (NH 4 ) 2 S 2 O 8 -NaHSO 3 Initiator; in step (1.2), the initiator is ammonium persulfate ((NH 4 ) 2 S 2 O 8 ).

[0017] Wherein, the molar ratio of acrylic acid, vinyl acetate, sodium methacrylate sulfonate and acrylamide is 4.5:0.2:4.5:1 to 1:0.1:1:1.

[0018] Wherein, in step (1), the dosage of polyelectrolyte is 5-10 mg / L high-salt wastewater.

[0019] Wherein, in step (2), the membrane surface flow rate of the mixed liquid in the electrodialysis membrane stack is 0.015 to 0.05 m / s.

[0020] Wherein, in step (2), the membrane surface flow rate of industrial tap water in the electrodialysis membrane stack is 0.015 to 0.05 m / s.

[0021] If the flow rate on the membrane surface is too small, it will not be conducive to reducing the thickness of the diffusion boundary layer, resulting in increased salt transport resistance and accelerated scaling rate on the membrane surface; if the flow rate on the membrane surface is too large, it may cause water molecules to enter the concentrated water chamber, affecting the final concentration effect.

[0022] Wherein, in step (3), the voltage applied between the cathode and the anode of the electrodialysis membrane stack is 5 to 15V.

[0023] The mechanism is: the polyelectrolyte can adsorb CaSO attached to the membrane surface 4 and Mg(OH) 2 The active sites on the surface of the crystal nucleus disrupt the arrangement and integration process of calcium and magnesium ions on the surface of the crystal nucleus, thereby effectively inhibiting the growth of the crystal nucleus on the membrane surface and achieving the effect of scale inhibition.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: By adding a trace amount (<10 mg / L) of polyelectrolyte into the dilute chamber of the electrodialysis membrane stack, the present invention can effectively prevent scaling on the membrane surface of the ion exchange membrane in the electrodialysis device and achieve a scale inhibition rate of 40% to 60% for calcium and magnesium ions. At the same time, when treating the same volume of wastewater, the electrodialysis device can reduce the operating energy consumption by about 15% and save about 20% of the operating cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 FTIR characterization diagram of the polyelectrolyte prepared in Example 1;

[0026] Figure 2 It is the structural principle diagram of the electrodialysis device;

[0027] Figure 3 is the scale inhibition rate of the electrodialysis device in Example 2 after operation using the method of the present invention;

[0028] Figure 4 It is the scale inhibition rate of the electrodialysis device in Example 3 after operating using the method of the present invention. DETAILED DESCRIPTION

[0029] Example 1

[0030] The preparation method of the polyelectrolyte of the present invention comprises the following steps:

[0031] (1) Add 6.48 g acrylic acid and 14.22 g sodium methyl methacrylate sulfonate to distilled water. After dissolving, gradually add saturated NaOH solution to the solution to neutralize the reaction solution. Adjust the pH of the reaction solution to 6-7. At this time, raise the temperature to 55°C and add initiator (NH 4 ) 2 S 2 O 8 -NaHSO 3 (the amount of the initiator added is 0.04% of the total mass of the acrylamide and sodium methacrylic acid sulfonate monomers), and the reaction is carried out at this temperature for 10 hours; the reaction product is purified by anhydrous ethanol, dried at 40°C, and crushed to obtain a white granular solid product;

[0032] (2) A four-necked flask was equipped with a stirrer, a reflux condenser, a thermometer and a dropping funnel; 2 g of the solid product of step (1) and 33 mL of water (the mass volume ratio of the solid product to water was 1 g:16.5 mL, i.e., 2 g of the solid product was added to 33 mL of water) were added into the flask; 1.42 g of acrylamide, 0.34 g of vinyl acetate and an initiator (NH 4 ) 2 S 2 O 8 Put it into a dropping funnel (the amount of initiator added is 0.075% of the total mass of the solid product, acrylic acid and vinyl acetate); heat the four-necked flask to 60°C, and add acrylic acid, vinyl acetate and initiator in the dropping funnel to the flask under stirring. After the addition is completed, keep it warm at the above temperature for 4 hours. After the reaction, reduce the temperature to below 40°C, discharge the material, and obtain a polyelectrolyte aqueous solution.

[0033] The structure of the polyelectrolyte prepared by the above method is shown in the following formula:

[0034]

[0035] The present invention forms a polyelectrolyte composed of four monomers, namely acrylic acid, vinyl acetate, sodium methacrylic acid sulfonate and acrylamide, through free radical polymerization. Figure 1 FTIR characterization of the structure of the polyelectrolyte synthesized in Example 1 showed that 3423.98 cm -1 For -NH 2 Stretching vibration peak, 1712.85cm -1 and 1642.5cm -1 Symmetric and asymmetric stretching vibration peaks of C=O, 1452.73 cm -1 is the stretching vibration peak of CN bond, 1204.10cm -1 and 1043.21cm -1 For-SO 3 - Symmetric and asymmetric stretching vibration peaks.

[0036] like Figure 2 As shown, the electrodialysis device used in the present invention includes an electrodialysis membrane stack, which is composed of several pairs of membrane groups, wherein cation exchange membranes and anion exchange membranes are alternately arranged between the anode and the cathode, and adjacent ion exchange membranes are separated by partitions to facilitate water distribution and collection.

[0037] Example 2

[0038] The inorganic salt ions in the desulfurization wastewater of a coal-fired power plant are recovered based on the polyelectrolyte prepared in Example 1, comprising the following steps:

[0039] (1) The ultrafiltration effluent of the desulfurization wastewater of the coal-fired power plant is passed into the fresh water chamber of the electrodialysis membrane stack, and a polyelectrolyte is added to the ultrafiltration effluent, and the amount of the polyelectrolyte added is 10 mg / L ultrafiltration effluent; industrial tap water is pumped into the concentrated water chamber of the electrodialysis membrane stack; the membrane surface flow rate of the mixed liquid in the electrodialysis membrane stack is 0.05 m / s; the membrane surface flow rate of the industrial tap water in the electrodialysis membrane stack is 0.05 m / s;

[0040] (2) An external DC power supply was connected, and the voltage applied between the cathode and anode of the electrodialysis membrane stack was 8 V. The electrodialysis device was operated under a constant voltage of 8 V. After 8 hours of operation, the conductivity of the desulfurized wastewater was reduced from 17.65 ms / cm to below 10 ms / cm.

[0041] After the operation is completed, the Ca in the fresh water chamber and the concentrated water chamber is tested 2+ Mg 2+ The difference in ion concentration is used to calculate the scale inhibition rate (the reduction ratio of calcium and magnesium ion loss before and after adding polyelectrolyte relative to the traditional electrodialysis concentration experiment). Figure 3 It can be seen that Ca 2+ Mg 2+The scale inhibition rates were 56.37% and 48.74% respectively. 3 The energy consumption of desulfurization wastewater is 6.08kW·h, which is higher than that of traditional electrodialysis method (i.e. Figure 2 The electrodialysis device of Example 2 is different from Example 2 in that the polyelectrolyte of Example 1 is not added to the ultrafiltration effluent) and the total cost (including the reagent cost of 0.1 yuan) is 6.62 yuan, which is 20.43% lower than the traditional electrodialysis method, as shown in Table 1.

[0042] Table 1

[0043]

[0044]

[0045] Example 3

[0046] The inorganic salt ions in the desulfurization wastewater of a coal-fired power plant are recovered based on the polyelectrolyte prepared in Example 1, comprising the following steps:

[0047] (1) The ultrafiltration effluent of the desulfurization wastewater of the coal-fired power plant is passed into the fresh water chamber of the electrodialysis membrane stack, and a polyelectrolyte is added to the ultrafiltration effluent at a rate of 5 mg / L of ultrafiltration effluent; industrial tap water is pumped into the concentrated water chamber of the electrodialysis membrane stack;

[0048] (2) An external DC power supply is connected, and a voltage of 8 V is applied between the cathode and anode of the electrodialysis membrane stack. The electrodialysis device is operated under a constant voltage of 8 V. After 10 h of operation, the conductivity of the desulfurized wastewater is reduced from 17.65 ms / cm to below 10 ms / cm.

[0049] After the operation is completed, the Ca in the fresh water chamber and the concentrated water chamber is tested 2+ Mg 2+ The difference in ion concentration is used to calculate the scale inhibition rate (the reduction ratio of calcium and magnesium ion loss before and after adding polyelectrolyte relative to the traditional electrodialysis concentration experiment). Figure 4 It can be seen that Ca 2+ Mg 2+ The scale inhibition rates were 50.01% and 46.77% respectively. 3 The energy consumption of desulfurized wastewater is 6.67 kW·h, which is 11.89% lower than that of traditional electrodialysis method; the total cost (including reagent cost of 0.05 yuan) is 6.85 yuan, which is 17.67% lower than that of traditional electrodialysis method, as shown in Table 2.

[0050] Table 2

[0051] <![CDATA[Energy consumption (kW·h / m 3 )]]> <![CDATA[Cost (yuan / m 3 )]]> Conventional electrodialysis process 7.57 8.32 Anti-scaling electrodialysis 6.67 6.85 .

Claims

1. A method for alleviating membrane scaling in ED, characterized in that: The steps include: (1) adding a polyelectrolyte to high-salinity wastewater to obtain a mixed solution; the polyelectrolyte is polymerized from acrylic acid, vinyl acetate, acrylamide and sodium methyl methacrylate sulfonate; The structure of the polyelectrolyte is shown below: ; (2) The mixed liquid is pumped into the fresh water chamber of the electrodialysis membrane stack, and the industrial tap water is pumped into the concentrated water chamber of the electrodialysis membrane stack; (3) Apply voltage between the cathode and anode of the electrodialysis membrane stack to concentrate and reduce the amount of high-salt water.

2. The method for alleviating membrane scaling in ED according to claim 1, characterized in that: The polyelectrolyte is prepared by the following method, which specifically comprises the following steps: (1.1) adding acrylic acid and sodium methacrylic acid to distilled water, and gradually adding saturated NaOH solution to the solution after dissolution, adjusting the pH value of the reaction solution to 6-7, raising the temperature to 55°C, adding an initiator to the reaction solution, and reacting at this temperature; the reaction product after the reaction is purified by anhydrous ethanol, and then dried to obtain a solid product; (1.2) adding the solid product of step (1.1) to deionized water, raising the temperature to 50-100°C, and dripping acrylamide, vinyl acetate and initiator into the above solution under stirring, and keeping the temperature for 1-6 hours after the dripping is completed; after the reaction, reducing the temperature of the reaction solution to below 40°C to obtain a polyelectrolyte aqueous solution.

3. The method for alleviating membrane scaling in ED according to claim 2, characterized in that: In step (1.1), the initiator is (NH4)2S2O8-NaHSO3 initiator; in step (1.2), the initiator is ammonium persulfate.

4. The method for alleviating membrane scaling in ED according to claim 2, characterized in that: The molar ratio of acrylic acid, vinyl acetate, sodium methacrylate sulfonate and acrylamide added is 1-4.5:0.1-0.2:1-4.5:

1.

5. The method for alleviating membrane scaling in ED according to claim 1, characterized in that: In step (1), the dosage of polyelectrolyte is 5-10 mg / L high-salt wastewater.

6. The method for alleviating membrane scaling in ED according to claim 1, characterized in that: In step (2), the membrane surface flow rate of the mixed solution in the electrodialysis membrane stack is 0.015~0.05m / s.

7. The method for alleviating membrane scaling in ED according to claim 1, characterized in that: In step (2), the membrane surface flow rate of industrial tap water in the electrodialysis membrane stack is 0.015~0.05m / s.

8. The method for alleviating membrane scaling in ED according to claim 1, characterized in that: In step (3), the voltage applied between the cathode and the anode of the electrodialysis membrane stack is 5 to 15.

Citation Information

Patent Citations

  • Stable water quality regulating waterway system based on inverse electrodialysis

    CN212315664U

  • Ionic membrane electro-deposition device with double cathode and anode switching

    CN212315716U

  • Device for removing ion in liquid by DC pulse electro-dialyzing

    CN2407824Y

  • Anti-scaling technology achieved through semipermeable membrane

    CN105585076A

  • The invention discloses an electrodialysis salt separation device and a high-salt wastewater treatment system

    CN208898568U